Sampling with Derivatives in Periodic Shift-Invariant Spaces. (29th September 2022) - Selvan, A. Antony; Ghosh, Riya
Abstract: We study the sampling problem involving derivatives in periodic shift-invariant spaces. We provide a necessary and sufficient condition for periodic nonuniform stable sampling with derivatives, based on block circulant matrices. Additionally, we derive an iterative algorithm to reconstruct a function from its irregular samples involving derivatives.